Odpowiedzi

2009-11-21T08:13:36+01:00
(x - 1) (x+3)>0
2x - 3x -x- 3>0
4x>3 |:4
x> 3/4





2009-11-21T08:23:45+01:00
(x-1) (x+3)>0
x-1 >0 ∧ x+3 >0
x>1 ∧ x>-3

(x-1)² (-x+2) (x-3)≥0
(x-1) (x+1) (-x+2) (x-3)≥0
x-1 ≥0 ∧ x+1≥0 ∧ -x+2≥0 ∧ x-3≥0
x≥1 ∧ x≥-1 ∧ -x≥-2 ∧ x≥3
x≥1 ∧ x≥-1 ∧ x≤ -2 ∧ x≥3


x³≥81x /:x
x²≥81
x²≥ √81
x²≥9
  • sm14
  • Początkujący
2009-11-21T08:23:46+01:00
(x-1)(x+3)>0
x2+3x-x-3=0
x2+2x-3=0
a=1 b=2 c= -3
delta= b2-4ac
delta = 2+12
delta = 14 wiec pierwiastek z delty równa sie pierwiastek z 14

dwa miejsca zerowe
b1=-2-pierwiastek z 14: 2=pierwiastek z 7
b2=-2+pierwiastek z 14:2= -pierwiastek z 7